Brown–McLean syndrome: the role of iridodonesis - Suwan Y (Dove Medical Press, 2016)
Yanin Suwan, Chaiwat Teekhasaenee, Kaevalin Lekhanont, Wasu Supakontanasan Department of Ophthalmology, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, Thailand Purpose: The aim of this study was to report a case series of Brown–McLean syndrome (BMS).Methods: The charts of 28 patients with BMS at Ramathibodi and Rutnin Hospital from 1981 to 2015 were reviewed.Results: BMS is a rare condition with corneal edema involving the peripheral cornea with orange-brown pigment deposition underlying the edematous area. The edema typically starts inferiorly and advances circumferentially to superior cornea. Central cornea remains clear in most patients. We report 28 patients with BMS that occurred either spontaneously or after various intraocular procedures. Ultrasound biomicroscopy was performed to demonstrate the iridocorneal relationship.Conclusion: Iridocorneal relationship from the ultrasound biomicroscopy study in four patients did not support previous hypothesis about the role of iridodonesis impact on corneal endothelium. Patients with BMS can rarely progress to corneal decompensation; however, they should be periodically monitored and made aware of early clinical signs of their complications. Keywords: Brown–McLean syndrome, peripheral corneal edema, marginal corneal edema, corneal decompensation